Loss of AKR1C1 is a good prognostic factor in advanced NPC cases and increases chemosensitivity to cisplatin in NPC cells. Issue 11 (19th April 2020) - Zhou, Chen; Shen, Guowen; Yang, Fan; Duan, Jingling; Wu, Zhen; Yang, Mingqing; Liu, Yi; Du, Xueli; Zhang, Xiaoling; Xiao, Shengjun
Abstract: Cisplatin resistance is one of the main obstacles in the treatment of advanced nasopharyngeal carcinoma (NPC). AKR1C1 is a member of the Aldo‐keto reductase superfamily (AKRs), which converts aldehydes and ketones to their corresponding alcohols and has been reported to be involved in chemotherapeutic resistance of multiple drugs. The expression and function of AKR1C1 in NPC have not been reported until now. The aim of this research was to investigate the expression of AKR1C1 and it is role in cisplatin resistance in NPC. AKR1C1 protein expression was detected by immunohistochemistry in human NPC tissues and by Western blot assays in NPC and immortalized nasopharyngeal epithelial cells. The effects of AKR1C1 knock‐down by siRNA on proliferation, migration and invasion in NPC cells were evaluated by CCK8, wound healing and transwell assays. To evaluate the effects of AKR1C1 silencing on cisplatin sensitivity in NPC cells, CCK8 assays were used to detect cell proliferation, flow cytometry was used to detect cell cycle distribution, and flow cytometry and DAPI staining were used to detect cell apoptosis. AKR1C1 down‐regulation was associated with advanced clinicopathological characters such as larger tumor size, more lymphatic nodes involvement, with metastasis and later clinical stages, while AKR1C1 down‐regulation was a good prognostic factor for overall survival (OS) in NPC patients. In vitro study showed that AKR1C1 was not directly involved in the malignant biological behaviours such as proliferation, cell cycle progression and migration of NPC cells, whereas AKR1C1 knock‐down could enhance cisplatin sensitivity of NPC cells. These results suggest that AKR1C1 is a potential marker for predicting cisplatin response and could serve as a molecular target to increase cisplatin sensitivity in NPC.